2014
DOI: 10.4236/crcm.2014.39110
|View full text |Cite
|
Sign up to set email alerts
|

Gangrenous Cholecystitis with Atypical Presentation in an Elderly Diabetic Woman

Abstract: In elderly patients, numerous factors subsidize the diagnostic challenge and high incidence of complications in this specific population, taking gangrenous cholecystitis as a critical example. The aim of this work is to report an unusual case of gangrenous choleystitis in an elderly diabetic women and its atypical clinical presentation. A 79-year-old female patient came to our observation; her medical history showed nausea and vomiting of about 2 hours which rapidly ended with symptomatic therapy, without recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In all previously reported cases of perforated GC, the patients were older (>65) and showed a cholecystitis complication (perforated or gangrenous gallbladder) as the first presentation; however, all of them were stable at presentation [9,[13][14][15]. Conversely, our patient exhibited septic shock as the first presentation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In all previously reported cases of perforated GC, the patients were older (>65) and showed a cholecystitis complication (perforated or gangrenous gallbladder) as the first presentation; however, all of them were stable at presentation [9,[13][14][15]. Conversely, our patient exhibited septic shock as the first presentation.…”
Section: Discussionmentioning
confidence: 66%
“…This report agrees with other similar case reports that highlight poorly controlled diabetes as a cause of late presentation complicated with cholecystitis and perforated gallbladder. Poorly controlled diabetes may obscure the patient's symptoms [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Fever, right upper quadrant pain, and jaundice consistent with Charcot’s triad and a positive Murphy’s sign are the most common presentation of a complicated AC [ 7 ]. However, atypical GC can present without the above findings and instead have minimal right upper quadrant tenderness or even a complete absence of pain [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this condition leads to life-threatening complications such as perforation, abscess formation, and peritonitis [3] , leading to high mortality [2] , accurate diagnosis and prompt surgical treatment are required. These patients generally present with intense abdominal symptoms such as abdominal pain; however, previous studies have reported that several patients with diabetes mellitus (DM) [ 4 , 5 ] and older patients [6] can develop GC without severe abdominal symptoms.…”
Section: Introductionmentioning
confidence: 99%